Forensic Monitoring Project Report: Brkanovo Brdo and Mostarsko Blato Exhumations of State Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The State Commission on Missing Persons conducted investigations at two locations at Brkanovo Brdo and three locations at Mostarsko Blato from 8-9 June 1998. No remains were recovered. These investigations were reportedly directed at the recovery of bodies buried at these locations in 1992 and/or buried or moved by UNPROFOR in 1993. Place of Exhumation: Brkanovo Brdo , Mostarsko Blato Date of Exhumation: 8-9 June 1998 Minimum Number of Exhumed Individuals: 000